Children referred for specialty care: Parental perspectives and preferences on referral, follow‐up and primary care. (3rd October 2016) - Freed, Gary L; Turbitt, Erin; Kunin, Marina; Gafforini, Sarah; Sanci, Lena; Spike, Neil
Abstract : Aim: Over the last decade, there has been a dramatic increase in the number of referrals for paediatric subspecialty care and in overall appointments (new and review) to these doctors. We sought to determine the perspective of parents regarding their role in the initiation of referrals, their preferences for follow‐up and the role of general practitioners (GPs) in care co‐ordination. Methods: Self‐completed survey in outpatient paediatric clinics (general paediatrics and four subspecialties) at two children's hospitals in Victoria. Recruitment targets were 100 parents in each of the general paediatrics clinics and 50 parents in each subspecialty clinic, equally divided between new and review visits (total n = 600). Results: A total of 606 parents provided responses, with a decline rate of 9%. Many (52%) new patients were referred by a GP with the remainder from a variety of other sources. With specific regard to providing general care to their child, only 45% were completely confident in a GP. Most (76%) agreed with the statement that a GP would give their child a referral to see a paediatrician whenever they ask. Approximately, a third of parents reported that a GP rarely or never co‐ordinates the care of their child with other doctors. Conclusions: Parents play an important role in both the initiation of paediatric specialty referrals and the patterns of follow‐up care provided. Parent perspectives, preferences and motivations on both the referral process and the patterns for ongoing care are essential to develop policies that provide the best and most efficient care for children.